2020
DOI: 10.1002/jsfa.10341
|View full text |Cite
|
Sign up to set email alerts
|

Changes in volatile flavor compounds of peppers during hot air drying process based on headspace‐gas chromatography‐ion mobility spectrometry (HS‐GC‐IMS)

Abstract: BACKGROUND Flavor plays a critical role in defining sensory and consumer acceptance of dried pepper, and it can be affected by temperature and moisture content during hot air drying (HAD). Thus, headspace‐gas chromatography‐ion mobility spectrometry (HS‐GC‐IMS) was used to analyze changes in volatile compounds of pepper during the HAD process with different drying temperatures. RESULTS A total of 45 volatile flavor compounds were identified, including 11 esters, 11 aldehydes, nine alcohols, five ketones, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 49 publications
2
29
0
1
Order By: Relevance
“…Headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) is a specific and simple method for identifying VOCs. Recently, HS-GC-IMS has been proven to be a helpful approach for analyzing and recognizing VOCs with different characteristics in foods, including dry-cured fish [11], Tricholoma matsutake Singer [12], sea cucumber peptide powders [13], peppers [14], and boiled Wuding chicken [15].…”
Section: Introductionmentioning
confidence: 99%
“…Headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) is a specific and simple method for identifying VOCs. Recently, HS-GC-IMS has been proven to be a helpful approach for analyzing and recognizing VOCs with different characteristics in foods, including dry-cured fish [11], Tricholoma matsutake Singer [12], sea cucumber peptide powders [13], peppers [14], and boiled Wuding chicken [15].…”
Section: Introductionmentioning
confidence: 99%
“…Combining IMS with other instruments is a more suitable and effective way to make better use of its advantages. Recently, headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) has been applied in detecting volatile compounds of fruits and vegetables, such as candied kumquats (Hu et al, 2019), jujube fruits (Yang et al, 2019), and dried peppers (Ge et al, 2020).…”
mentioning
confidence: 99%
“…Alcohols are produced by the oxidation and decomposition pathways of grease and lipid, and 3-Methyl-1-butanol is the side product from the alcohol fermentation of starch and sugar. Ge et al [37] also found that the content of 3-methyl-1-butanol was significantly increased in hot drying peppers. The thermal oxidation of polyunsaturated fatty acids or the thermal degradation of amino acids produced ketones.…”
Section: Hs-gc-ims Analysismentioning
confidence: 92%